Ocular findings of albinism in DYRK1A-related intellectual disability syndrome. (1st November 2020) - Ernst, Julia; Alabek, Michelle L.; Eldib, Amgad; Madan-Khetarpal, Suneeta; Sebastian, Jessica; Bhatia, Aashim; Liasis, Alkiviades; Nischal, Ken K.
ABSTRACT: Background: Pathogenic variants in DYRK1A are associated with DYRK1A -related intellectual disability syndrome (DIDS). Common features of this diagnosis include microcephaly, intellectual disability, speech impairment, and distinct facial features. Reported ocular features include deep-set eyes, myopia, and strabismus. We present a case of DYRK1A -related intellectual disability syndrome with ocular findings of albinism and explore the possible pathogenesis of this previously unreported manifestation. Materials and Methods: This is a single, retrospective case report of a child with DIDS who underwent an ophthalmic exam including detailed visual electrophysiology. Results : A 21-month-old female with microcephaly, failure to thrive, language delay, cleft palate, and cardiac defects had an ophthalmic exam showing myopia, strabismus, a hypopigmented fundus and crossed asymmetry on visual evoked potential (VEP), consistent with ocular findings of albinism. Whole exome sequencing identified a pathogenic DYRK1A variant; no albinism gene variants were reported. Her constellation of features is consistent with a diagnosis of DYRK1A -related intellectual disability syndrome; however, ocular features of albinism have not previously been reported in this condition. Conclusions: This is, to the best of our knowledge, the first report of ocular findings of albinism in a case of DYRK1A -related intellectual disability syndrome. We propose that ocular albinism is a novel ocular phenotype of DYRK1A -related disease. Ophthalmic exams in patients with this diagnosis should include thorough evaluation for ocular albinism, including VEPs.